INFORMATION SUPPORT FOR ENTERPRISES AND INSTITUTIONS OF THE AVIATION COMPLEX IN THE FIELD OF QUALITY ASSURANCE PRODUCTS AND SERVICES - Solomentsev , O. V.; Litvin A. M., A. M. (Problems of Informatization and Management, 2021)
The goals and general structure of the system of information support of enterprises and institutions of the aviation complex in the field of quality assurance of products and services, the main requirements to the system in terms of content and its information resources are defined.